2021
DOI: 10.1039/d0sc05118g
|View full text |Cite
|
Sign up to set email alerts
|

Bridging photochemistry and photomechanics with NMR crystallography: the molecular basis for the macroscopic expansion of an anthracene ester nanorod

Abstract: Crystals composed of photoreactive molecules represent a new class of photomechanical materials with the potential to generate large forces on fast timescales. An example is the photodimerization of 9-tertbutyl-anthracene ester (9TBAE)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…[43,48] It seems that solid-state dimerization leads to adifferent dimer crystal polymorph, as observed in other anthracene derivatives. [49] In the Supporting Information, we present solid-state NMR data that is consistent with this possibility,but since the current paper focuses on the reaction dynamics,d etailed characterization of the crystal produced by solid-state photodimerization must be reserved for future work. Eventually, the quantitative prediction of the crystal expansion/contraction will require precise determination of this crystal packing and orientation.…”
Section: Methodsmentioning
confidence: 85%
“…[43,48] It seems that solid-state dimerization leads to adifferent dimer crystal polymorph, as observed in other anthracene derivatives. [49] In the Supporting Information, we present solid-state NMR data that is consistent with this possibility,but since the current paper focuses on the reaction dynamics,d etailed characterization of the crystal produced by solid-state photodimerization must be reserved for future work. Eventually, the quantitative prediction of the crystal expansion/contraction will require precise determination of this crystal packing and orientation.…”
Section: Methodsmentioning
confidence: 85%
“…NMR parameters derived from the CS and EFG tensors have been used extensively in molecular structure refinement (Olsen et al, 2003;Witter et al, 2006;Harris et al, 2010;Apperley et al, 2012;Harper et al, 2013;Kalakewich et al, 2015;Yang et al, 2016;Soss et al, 2017;Chalek et al, 2021;Wang et al, 2021). Recently, plane-wave EFG tensor predictions involving 14 N, 17 O, and 35 Cl nuclei were used to obtain optimized damping parameters for crystal geometry refinement using Grimme's DFT-D2 scheme (Holmes and Schurko, 2018).…”
Section: Modeling Disorder In the 4-nitrobenzaldehyde Crystal Structurementioning
confidence: 99%
“…SSNMR investigations are often coupled with X-ray diffraction and first-principals calculations to form the interdisciplinary field of NMR crystallography. The success of NMR crystallography has been greatly facilitated by the availability of accurate computational methods for predicting NMR parameters which typically employ density functional theory (DFT) (Gervais et al, 2005;Wu, 2008;Kong et al, 2013;Yang et al, 2016;Kong et al, 2017;Soss et al, 2017;Holmes and Schurko, 2018;Yamada et al, 2020;Chalek et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The first example of the large photomechanical expansion of organic molecular crystals was reported by Bardeen et al, who observed an average 8% expansion of 9- tert -butyl-anthracene ester (9TBAE) nanorods . Subsequent studies suggested that the 9TBAE nanorod expansion did not result from the molecular volume change but instead resulted from the rearrangement of molecular contents. , Recent studies have shown that molecular orientation is coherently correlated with photomechanical behavior and photochemical dynamics. , For our ( E )- NAAM hollow microcrystals, the significant molecular geometry and structural changes from parallel stacking monomeric pairs to butterfly-like photodimers satisfy the first prerequisite for expansion (Figure S19). Although there was no direct comparison between the crystal volume of the monomer and the photoreacted dimer, the formation of the highly distorted photodimer suggests that the crystal lattice might have experienced expansion during photodimerization.…”
Section: Results and Discussionmentioning
confidence: 76%